Increased Cervical Cancer Risk Associated With Screening at Longer Intervals. Issue 2 (February 2015) - Kinney, Walter; Wright, Thomas C.; Dinkelspiel, Helen E.; DeFrancesco, Mark; Thomas Cox, J.; Huh, Warner
Abstract : The 2012 national recommendations for cervical cancer screening will produce a lower level of cervical cancer protection than previously afforded by annual cytology or 3-year cotesting. After a single negative cotest result, the risk of cervical cancer is twice as large at 5 years as it is at 3 years. Modeling published since the 2012 guidelines were drafted indicates that extending the cotesting screening interval from 3 to 5 years at ages 30–64 years will result in an additional 1 woman in 369 compliant with screening receiving a cervical cancer diagnosis during her lifetime, and an additional 1 in 1, 639 dying of cervical cancer. The authors believe that a significant number of patients and providers would not choose to accept these additional risks if they understood them, despite the recognition of potential harms associated with more intensive screening. Abstract : The 2012 national recommendations for cervical cancer screening will produce a lower level of cervical cancer protection than previously afforded by annual cytology or 3-year cotesting.